Do communicative language teaching (CLT) activities help increase students' speaking performance? - Abulqasem, Eman Abdussalam Owen; Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This paper aims to propose a study to investigate the effectiveness of selected communicative activities used in the classroom, such as language games and information-gap activities on Libyan students’ communicative skills. From the literature review it is found that Libyan students usually are not eager to speak and communicate in the foreign language because of shyness, afraid of making mistakes, low proficiency levels, or having limited chances to practice the language. The Libyan curriculum is based on Communicative language teaching (CLT), which is an approach that emphasizes on communication but some teachers do not follow the approach because they do not believe it is effective (Al-Buseifi, 2003). In the current study the researcher proposes to study 60 participants from two Libyan schools located in Malaysia through an embedded experimental model mixed-method design. By proposing to do a research using a quasi-experimental research that utilizes a pre-test, treatment and then a post-test on a non-randomized control group, as well as doing observations and focus group discussions, we hope to understand the effectiveness of using selected communicative activities on Libyan secondary school students’ speaking performance. The research also proposes to learn students’ reactions and perceptions towards CLT and the activities based on its principles. It is hoped that the results from this proposed research will provide an understanding, for students, teachers and curriculum decision makers, of the role that CLT activities play on speaking performance.